ANALISIS YURIDIS FUNGSI DAN PERAN TENAGA PENDIDIK DALAM PEMBENTUKAN BINTARA DI SPN POLDA METRO JAYA - heri sutanto; Dadang Suprijatna; Nurwati Nurwati (JURNAL HUKUM DE'RECHTSSTAAT, 2020)
Police efforts in achieving the educational goals has not come true as well. Jakarta Police SPN even further behind the other Police-Police found in Indonesia. Indicators not maximal achievement of educational goals Police use them visible on the lower end of the exam results Education and Formation (Diktuk) Police Officer Polda Metro Jaya on the NES. The role of educators is expected to print the candidates NCO Professional Police so that they can run their police duties properly in accordance with the ethics of the police which is based on the Tribrata. The method used in this research is the method of juridical sociological (empirical). The establishment of the Police Officer Education is an education to establish and equip students to be members of the police who have the knowledge, skills, abilities, commendable attitude and behavior in the context of carrying out police duties that come from the general public with the lowest level of high school graduates who have passed the various required tests such as administration and others.